Study on Mass Movement Risk Area in The Manoel Pimenta Neighborhood in the City of Teófilo Otoni/MG (International Journal of Geoscience, Engineering and Technology, 2024)
Brazil is a country with great climatic, geological and socioeconomic diversity. One of the main problems faced in urban centers is the occupation of land, mostly by an economically vulnerable population, in areas at risk of movement of massive soil or in areas of flooding, putting them at risk of material, health and life. This work aims to identify, classify and recommend technical solutions in an area at risk of slope sliding in the Manoel Pimenta neighborhood, in the city of Teófilo Otoni. A history of mass movement and the imminence of new mass movement were noted in the study area, where there are 3 residences, all classified as R4 (High Risk), requiring intervention from public bodies and owners to mitigate risks.